Systematics of a Sea cucumbers of the Genus Holothuria (Aspidochirotida: Holothuroidea)and Phylogeography in H. Ieucospilota based on the Cytochrome-b Gene - Kamarudin, Kamarul Rahim (Sea Cucumber (Echinodermata: Holothuroidea) Research Group, 2010)
We have incorporated a morphological approach using ossicles of sea cucumber (Echinodermata: Holothuroidea) and partial sequences of 16S ribosomal RNA (rRNA) gene and cytochrome c oxidase I (COI) gene in this study as addition to partial cytochrome b (cyt b) mitochondrial DNA (mtDNA) gene sequences for species identification. Beside Holothuria species including Holothuria leucospilota, species from other genera were also included in order to get a better view on the phylogenetic relationship of Holothuria species. 27 partial sequences of 16S rRNA mtDNA gene (Accession No.: FJ223854 FJ223872) and COI mtDNA gene (Accession No.: FJ223873 - FJ223880) have been registered with GenBank, National Center for Biotechnology Information (NCBI), U.S. National Library of Medicine (http://www.ncbi.nlm.nih.gov/) prior to publications. Sea Cucumber Database, Kulliyyah of Science, International Islamic University Malaysia ( http://sea.cucumber.kos.iium.googlepages.com/) containing all results of this study the first online database on sea cucumber in Malaysia has been developed and the database can also be accessed worldwide from Malaysia Maritime Database (http://marin-dbase.com/).